Policy-making process in the education system (Case study: Faculty of Medical Sciences, Islamic Azad University of Mashhad) - Mahbobeh Montazer Ataei; Hossein Karimi Moonaghi (Mashhad University of Medical Sciences, 2022)
Background: The purpose of this study is to design a model for the policy-making process in the education system of the Faculty of Medical Sciences at the Islamic Azad University.Methods: The research method used in this study is mixed. A mixed-methods sequential explanatory design is used to illustrate the methodological discussion. In the qualitative phase, data-based theorizing was done; and in the quantitative part, field research was fulfilled. The sample of the qualitative section consisted of 14 members of the board of trustees of the Azad University selected via purposive sampling.  As with the quantitative section, the statistical population was 110 faculty members of the Faculty of Medical Sciences at Mashhad Azad University from whom 86 ones were adopted through simple random sampling method.Results: The research findings related to the qualitative phase were the presentation of a policy model in the education system that includes 47 components, 19 subcategories, and 6 main categories. Further, the results obtained from the quantitative phase revealed that social entrepreneurship, as the central category of research, is above average in the educational system of the Faculty of Medical Sciences at Islamic Azad University, Mashhad branch.Conclusion: According to the theorizing in the research model, it can be concluded that conditions such as social surveying, centralized system, actors, and policy model cause social entrepreneurship to be formed as a central category in education system policy. Strategies such as knowledge-based economics, strategic management, effectiveness, and futures studies as strategies of the education system lead to inclusive employment, professional ethics, social responsibility, and training of skilled manpower.